A Connected Network of Interacting Proteins Is Involved in Human-Tau Toxicity in Drosophila - Feuillette, Sébastien; Charbonnier, Camille; Frebourg, Thierry; Campion, Dominique; Lecourtois, Magalie (Frontiers in Neuroscience, 2020)
Tauopathies are neurodegenerative diseases characterized by the presence of aggregates of abnormally phosphorylated Tau. Deciphering the pathophysiological mechanisms that lead from the alteration of Tau biology to neuronal death depends on the identification of Tau cellular partners. Combining genetic and transcriptomic analyses in Drosophila, we identified 77 new modulators of human Tau-induced toxicity, bringing to 301 the number of Tau genetic interactors identified so far in flies. Network analysis showed that 229 of these genetic modulators constitute a connected network. The addition of 77 new genes strengthened the network structure, increased the intergenic connectivity and brought up key hubs with high connectivities, namely Src64B/FYN, Src42A/FRK, kuz/ADAM10, heph/PTBP1, scrib/SCRIB and Cam/CALM3. Interestingly, we established for the first time a genetic link between Tau-induced toxicity and ADAM10, a recognized Alzheimer Disease protective factor. In addition, our data support the importance of the presynaptic compartment in mediating Tau toxicity.